How manager solve the risks in the management / Siti Norumia Yaakob - Yaakob, Siti Norumiah (Faculty of Information Management, 2014)
Considers many demands facing managers in innovative arrangements, especially watching the effects of downsizing and flattened organizational structures. Managers have to be concerned with, the risk that they need to face in a service quality, financial planning and accountability organizational change, project management, efficient use of resources, teamwork and leadership, stress and many more.